Increased frequency of canine distemper virus‐specific antibodies in multiple sclerosis. Issue 1 (10th December 2020) - Rohowsky‐Kochan, Christine; Davidow, Amy; Dowling, Peter; Cook, Stuart D.
Abstract: Background and purpose: Canine distemper virus (CDV) is a candidate agent in the etiology of multiple sclerosis (MS). Elevated anti‐CDV levels were previously found in the sera from MS patients compared with controls. We now investigated whether there was an age‐related association with the presence of antibodies specific to CDV‐hemagglutinin (H) protein in MS. Methods: Sera from patients with MS, other neurological diseases, and inflammatory and/or autoimmune diseases, and healthy individuals were screened for anti‐CDV in an ELISA using linear peptides of the CDV‐H protein as antigen. Antibody levels to measles and varicella‐zoster virus were measured and served as controls. Results: Analysis of the new cohort of MS patients and controls confirmed our initial finding of elevated anti‐CDV‐H levels in MS patients. An increase in measles but not varicella‐zoster virus antibody levels was found in MS patients compared with healthy controls. Data from the new cohort of patients and controls were combined with data from the original study and analyzed with respect to age distribution of anti‐CDV IgG. Mean CDV antibody levels were significantly elevated in each decade from 20 to 50 years of age in MS compared with healthy and disease controls. Antibody levels to measles virus were not consistently elevated during this age span. A striking relationship ( p < .0001, odds ratio = 5.0) was observed between elevated anti‐CDV‐H levels and diagnosis of MS. Conclusions: The finding that anti‐CDV levels are elevated in MS patients of all ages provides substantial evidence of a strong association between elevated anti‐CDV and MS. Abstract : We provide evidence that canine distemper virus is associated with patients with multiple sclerosis. Antibodies to this virus were found in multiple sclerosis patients throughout many decades.